Bimbingan & Pelatihan KTI (Karya Tulis Ilmiah) Bagi Siswa-Siswi Smp Negeri Di Kabupaten Ketapang - Betti Ses Eka Polonia; Ahmad Ravi; Alfath Desita Jumiar (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
PKM programs are implemented to increase students' creativity in writing scientific papers improve critical thinking skills and problem-solving abilities. The implementation of PKM has presented information in the implementation of training activities and guidance for writing scientific papers. It can equip students to take part in regional and national LKTIs. The materials presented during the training were: 1) Understanding of KTI; 2) Preparation of KTI; 3) KTI Preparation Practice, and 4) Sharing and assistance in the preparation of KTI. At the end of the activity, 70% of students are expected to be able to make a KTI design. Furthermore, of the students who made the KTI design, 50% of them succeeded in making a scientific paper and were included in the regional and national LKTI